Analyse De L’état De La Diversité Floristique Des Plateaux Suivant Un Gradient D’aridité Nord- Sud Dans La Réserve De Biosphère Du W Du Niger - Jazy, Mamadou Aïssa; Douma, Soumana; Mahamane, Ali; Mahamane, Saadou (European Scientific Journal, ESJ, 2018)
Introduction: In Niger, the degradation of ecosystems leads to a loss of biodiversity and an increase in the adverse effects of climate change, especially in the ecosystems contracted from the plateaux of the Niger W biosphere reserve. Objective: The objective of this study is to characterize the spatial variability of the flora according to the north-south rainfall gradient of the reserve. Methodology: Phytosociological surveys, an ascending hierarchical classification and a canonical analysis of correspondences between plant groups and environmental factors. Results-Discussion: The 126 inventoried species have 88 dicotyledons, 28 woody species, and 98 herbaceous species. The most common families are: Poaceae (21.42%), Fabaceae (12.69%), Rubiaceae (7.14%) and Convolvulaceae (6.34%). The biological spectrum is dominated by therophytes then microphanerophytes. The world chorology is marked by African species followed by palaeotropics or pantropicales, and at the African level, Sudano-Zambezian species are the most frequent. The presence of intermediate species (GC-SZ and GC-SZ-SahS) is noted. From north to south, 3 groups of plants were highlighted: the group with Sida cordifolia and Guiera senegalensis whose phytodiversity is reduced; Group II consisting of the subgrouping with Combretum nigricans and Microchloa indica and the subgrouping with Combretum micranthum and Gardenia sokotensis floristically rich, with however a regeneration dominated by Guiera senegalensis; grouping with Loudetia togoensis and Acacia macrostachya, in good state of conservation. Conclusion: The study made it possible to characterize floristically the various landscapes along the rainfall and anthropic gradient. Thus, in view of the structures of the stands observed, the distribution of floristic diversity increases according to a gradient of decreasing aridity from the periphery to the internal part of the reserve. From the north to the south there is a degraded part, a part gradually invaded by Guiera senegalensis and another well preserved. This work, which provides an overview of the state of conservation of the floristic diversity of the Niger W Biosphere Reserve, allows taking appropriate measures to safeguard our plant resources.